New method of gas drainage as a solution of danger phenomena in underground coal mines (Rudarsko-geološko-naftni zbornik, 2017)
The further development of coal mining in different countries and in India is connected with many problems. Very serious are emission of gas, sudden outbursts of gas and coal, mine fires, dustiness, spontaneous combustion, methane concentration. The article deals with these problems solving. It describes the new method applied in coal mines in the Czech Republic that has brought very good results.